ULTRATHIN CARBON FILMS ON SAPPHIRE GROWN BY LASER ABLATION: SYNTHESIS AND AFM-STUDY - Viktor V. Ilyasov; Besarion C. Meskhi; Anatoly A. Ryzhkin; Igor V. Yershov (Advanced Engineering Research)
The synthesis technique of ultrathin films on sapphire by laser ablation, and the results of their study by the atomic force microscopy (AFM) method are stated.